Construction boom coming to an end: Change in policy strategy needed - Martin Gornig; Laura Pagenhardt (DIW Weekly Report, 2023)
Following the construction boom of recent years in Germany, inflation and supply bottlenecks hit the industry hard in 2022. While nominal construction volume increased by nearly 14 percent, it decreased by two percent when adjusted for inflation. Residential construction, which is urgently needed, was particularly affected. In 2023 and 2024, it is expected that investors will show restraint and that nominal construction volume will only grow by four to five percent due to rising construction costs and worsening financing conditions. However, the core construction industry should also benefit from the upturn in construction activity, particularly in commercial and public sector construction. The decrease in real construction volume is putting policymakers under enormous pressure and requires a strategy change. Key policy goals can only be achieved if construction capacities are significantly expanded, not shrunk. Policy should focus in particular on incentives for the redensification of existing buildings, for energy-efficient refurbishment, and for expanding municipal infrastructure.
Keywords: E32; E66; 330; Construction industry; residential construction; public infrastructure; economic outlook